Deforestation in Brazil:: A controversy in 50 Shades of Green - Benevides, Maria; Almeida, Lalo (Sustainability in Debate, 2015)
Brazil slashed deforestation in the Amazon Forest, but has now been stuck for a few years around an annual record of 5,000 square km ”“ an area bigger than three times the size of São Paulo municipality, according to the Satellite Deforestation Monitoring Project of the Legal Amazon (Prodes).